The Impact of Revenue From Contracts With Customers on Financial Performance - Wulandari, Defi; Aziza, Nurna (SIMAK, 2024)
This research aims to disseminate the impact of implementing IFRS 15 on company financial performance, with a focus on property and real estate companies in Indonesia listed on the Indonesia Stock Exchange (BEI) and similar companies on the Stock Exchange of Thailand (SET) during the period 2018-2021 observations for companies in Indonesia and 2017-2020 for Thai companies. The research sample was 46 companies selected using the purposive sampling method. This research uses a comparative method to compare financial performance before and after the implementation of IFRS 15. Data analysis was carried out using the paired sample t-test or Wilcoxon test. The research results show that after the implementation of IFRS 15, profitability ratios (NPM, ROA and ROE) show a decline compared to before. On the other hand, the solvency ratio (DAR and DER) showed an increase, and the liquidity ratio (CR) decreased compared to the period before the implementation of IFRS 15.